Analisis Penggunaan Modul Belajar Kurikulum Darurat pada Pembelajaran Siswa Kelas V SD Inpres 10/73 Pancaitana - Makmur Nurdin; Awaluddin Muin; Riska Andriani (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
The problem in this study is to find out the description of the use of the Emergency Curriculum Learning Module in the learning of fifth grade students of SD Inpres 10/73 Pancaitana. This research is a descriptive qualitative research. The results of data analysis show that the use of the Emergency Curriculum Learning Module which consists of a Companion Module for Students, an Assistance Module for Parents, and a Facilitator Module for Teachers in the fifth grade student learning of SD Inpres 10/73 Pancaitana is available in electronic form and already supports the literacy learning process. and student numeration during the pandemic. In addition to its use, it has advantages and disadvantages. The conclusion of this research is that the use of Emergency Curriculum Learning in the learning of fifth grade students of SD Inpres 10/73 Pancaitana has been running but still needs to be optimized. The problem with using the module which is only available in electronic form that requires additional learning facilities is rooted in the risk of misuse of cellphones for students both at school and at home as well as the large number of additional costs for implementing learning